Kedudukan Shalat Sunnah Qabliyyah Jumat Dalam Pemikiran Hukum Imâm Al-Nawawî - Rizky Muktamirul Khair; Busyro Busyro (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
The firm stipulation of sunnah qabliyah prayer is not found in the hadith of the Prophet, but among the scholars of the Shafi'yah, such practice is still carried out by likening it to other fardhu prayers. The practice has been studied extensively by Shafi'yah scholars, and one of them is Imâm al-Nawawî. The question asked in this discussion is the rationale of Imâm al-Nawawî in establishing the law of sunnah law for the prayer and when its execution time. According to Imâm al-Nawawî, the argumentis the generality of hadith announcement about sunnah rawatib prayer and the use of qiyas between Zuhr prayer and Jumat prayer. The general argument is more valid and strong compared with other postulates. As for the time of its implementation, sunnah qabliyyah prayerfor Jumat prayer may be done if there is the first azan when zawâl. Whereas if only one azan, may pray two rak'ah with the intention of sunnah qabliyyahbefore Jum’ah prayer together with tahiyyatul masjid prayer for the new arrival at khutbah. As for those who have sat before the khutbah, it is enough with sunnah muthlaq prayer.